2017
DOI: 10.1002/elps.201600376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of overlapping electric double layer on mass transport of a macro‐solute across porous wall of a micro/nanochannel for power law fluid

Abstract: Effects of overlapping electric double layer and high wall potential on transport of a macrosolute for flow of a power law fluid through a microchannel with porous walls are studied in this work. The electric potential distribution is obtained by coupling the Poisson's equation without considering the Debye-Huckel approximation. The numerical solution shows that the center line potential can be 16% of wall potential at pH 8.5, at wall potential -73 mV and scaled Debye length 0.5. Transport phenomena involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In the above context, the liquid slip occurs over the hydrophobic surface [201] for the significant zeta potential in electrolyte solutions. By combining electrokinetic and pressuredriven with the first-order Navier's slip condition, the oscillating flow in rectangular [202][203][204][205][206][207] and circular [208][209][210] microchannels increased the flow efficiency. It was found that 10% slip length in a specific electrolyte solution enhances the flow rate by 20%.…”
Section: Slip/jump On Electrokinetic Flowmentioning
confidence: 99%
“…In the above context, the liquid slip occurs over the hydrophobic surface [201] for the significant zeta potential in electrolyte solutions. By combining electrokinetic and pressuredriven with the first-order Navier's slip condition, the oscillating flow in rectangular [202][203][204][205][206][207] and circular [208][209][210] microchannels increased the flow efficiency. It was found that 10% slip length in a specific electrolyte solution enhances the flow rate by 20%.…”
Section: Slip/jump On Electrokinetic Flowmentioning
confidence: 99%
“…The gating voltage not only alters the transverse electric field distribution in the nanochannel due to the double layer effect [40] but also impacts the lateral electric field and thus the electrophoretic force. Consequently, varying the gating voltage magnitude would have an impact on the molecular flux and transfer efficiency.…”
Section: Impact Of Gating Voltage Magnitude On the Transfer Efficiencymentioning
confidence: 99%
“…Since the advent of nanoscience in the 1980s, it has received a lot of attention from governments and scholars, whose purpose is to determine the flow behavior of confined fluids in the nanochannels such as nanotubes and nanopores to assist production activities. The most important feature of fluids in nanochannels is that the strong wall effects make the fluid properties at the interface different from that in the bulk phase. Many novel phenomena during the water and ion transport processes have been discovered, such as overlapping electric double-layer structures, and wall slip . Michaelides and Morgenstern identified and explained a competition between the ability of water molecules to simultaneously bond to the substrate and to accept hydrogen bonds through a combination of low-temperature scanning tunneling microscopy (STM) experiments and first-principles electronic structure calculations .…”
Section: Introductionmentioning
confidence: 99%